Agricultura familiar e cadeias curtas: dinâmicas econômicas, sociais e culturais na Feira Livre Comunitária de Dom Pedrito, RS - (:unkn) unknown (Universidade Federal do Pampa, 2017)
The objective of this work was to evaluate the contribution of the Community Free Fair of Dom Pedrito in the socio-economic condition of the family farmers interviewed. Thus, through interviews conducted at the fair between the months of April and May 2017 were interviewed nine family farmers integrated to the fair. From the record of the interviews and the technique of speech analysis sought to identify characteristics of the family farmers who are part of the fair, the factors that motivated them to be part of it, as well as identifying those marketed by them and the origin of these products. Moreover, it was analyzed how the fair represents an alternative to market access and production of farmers/Fairers interviewed to the extent to contribute to maintaining spending and promoting better quality of life for them. Among the main results it is noted that the presence of several members of the families of the respondents working at the fair, people with different personal characteristics, among them young, retired, married, singles, etc. It was also noted that access to the fair on the part of family farmers was motivated by a possibility of incrementing in income and to be part of the fair's living environment. The fair represents an important alternative to market access and disposal of the products produced by the interviewed family farmers, products that could be found to be production of the fairers themselves. In this context, it is noteworthy that the Community free trade Fair of Dom Pedrito has an important contribution to maintaining spending and accessing the quality of life of families of family farmers/trade fairs interviewed
Keywords: Mercados alternativos; Produção familiar; Qualidade de vida; Alternative markets; Familiar production; Quality of life; CNPQ::CIENCIAS AGRARIAS